Chloe & Cartoon. 2, It's a cat thing - Tessier, Greg (Charmz, 2021)
Chloe Blin and her family have just adopted a kitten named Cartoon, and they soon discover what it takes to raise a cat. First, they take Cartoon to his first vet appointment, and he encounters their neighbor's dog, Smooch. Then, Cartoon explores the great outdoors and meets some fellow felines.